The Hasty British Ban on Commercial Surrogacy - Brahams, Diana (The Hastings Center report, 1987)
While commercial surrogate parenting arrangements continue to flourish in the U.S., Britain has made it a criminal offense for third parties to benefit from surrogacy. Voluntary surrogacy, however is still within the law. Banning commercial surrogacy while leaving voluntary surrogacy lawful seems neither logical nor fair. A more equitable solution would be to license stringently and control both commercial and nonprofit agencies to provide these services.